PERMINTAAN KONSUMEN TERHADAP SAYURAN ORGANIK DI PASAR PULAU SAPARUA - Natelda R. Timisela; Marfin Lawalata; Valenszya Jozias; Febby J Polnaya; Stevianus Titaley (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
The purpose of the study was to analyze consumer demand for organic vegetables in Saparua Island, Central Maluku Regency. Organic vegetables are environmentally friendly and more to the concept of nature (back to nature). The research sampling technique was done by accidental sampling. The number of research sample was 40 people. Based on the ANOVA test results obtained F-count 17.630> F-table 2.64 means that the price of organic vegetables, the price of non-organic vegetables, income, and family members simultaneously have a significant influence on consumer demand for organic vegetables in Saparua Island. However, partial testing shows that the variables that significantly effect on demand for organic vegetables are the price of organic vegetables, the price of non-organic vegetables, the number of family members, the taste and frequency of purchase.